Considerations for Developing Effective Herbicide Prescriptions for Forest Vegetation Management - Anna Osiecka; Patrick Minogue (EDIS)
Developing a herbicide treatment prescription is a complex process that involves matching a suitable herbicide program with a specific silvicultural operation and an overall management objective. This revised 8-page fact sheet reviews important considerations in developing effective and environmentally sound herbicide recommendations for managing vegetation in forests. It is intended for use by private forest landowners, foresters, and other land managers. Written by Anna Osiecka and Patrick J. Minogue and published by the UF Department of School of Forest Resources and Conservation, May 2011.